Hydroxycarboxylic Acid Receptor 1 and Neuroprotection in a Mouse Model of Cerebral Ischemia-Reperfusion - Buscemi, Lara; Blochet, Camille; Magistretti, Pierre J.; Hirt, Lorenz (Frontiers in Physiology, 2021)
Lactate is an intriguing molecule with emerging physiological roles in the brain. It has beneficial effects in animal models of acute brain injuries and in traumatic brain injury or subarachnoid hemorrhage patients. However, the mechanism by which lactate provides protection is unclear. While there is evidence of a metabolic effect of lactate providing energy to deprived neurons, it can also activate the hydroxycarboxylic acid receptor 1 (HCAR1), a Gi-coupled protein receptor that modulates neuronal firing rates. After cerebral hypoxia-ischemia, endogenously produced brain lactate is largely increased, and the exogenous administration of more lactate can decrease lesion size and ameliorate the neurological outcome. To test whether HCAR1 plays a role in lactate-induced neuroprotection, we injected the agonists 3-Chloro-5-Hydroxybenzoic acid and 3,5-Dichloro-Hydroxybenzoic acid into mice subjected to 30-minutes middle cerebral artery occlusion. The in vivo administration of HCAR1 agonists at reperfusion did not appear to exert any relevant protective effect as seen with lactate administration. Our results suggest therefore, that the protective effects of lactate after hypoxia-ischemia come mainly from the metabolic effects of lactate over its signaling through HCAR1. It is possible that high concentration of endogenous lactate combined with high-affinity HCAR1 agonists, which are not transported into the cells and may remain in the interstitial space reaching high local concentrations, could overstimulate neuronal HCAR1 and prevent potential signaling-related beneficial effects.